The Influence of Brand Image, Price, and Product Quality on Customer Loyalty to Glad2Glow Products : (A Study of Glad2Glow Instagram Followers) - Fani, Rista Adhalia; Kusumasari, Indah Respati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the influence of brand image, price, and product quality on customer loyalty to Glad2Glow products, Products (A Study of Glad2Glow Instagram Followers). The research applies a quantitative approach using a survey method, involving 100 respondents who are Glad2Glow Instagram followers and have purchased the products at least twice. Data were collected through questionnaires measured on a Likert scale and analyzed using multiple linear regression with SPSS 31.0. The findings show that brand image and price have a positive and significant effect on customer loyalty, while product quality does not have a significant impact. Simultaneously, the three variables are proven to influence customer loyalty, as indicated by the results of the F-test. These results highlight the importance of strengthening brand image and implementing appropriate pricing strategies to enhance loyalty in a highly competitive skincare industry. On the other hand, the insignificant role of product quality indicates that consumers’ loyalty toward Glad2Glow is more strongly driven by perceptions of brand reputation and affordability rather than product performance. The study suggests that future research expand the scope of variables such as promotion, trust, or satisfaction to provide a more comprehensive view of customer loyalty factors.